Semantic-Service Provisioning for the Internet of Things - Bimschas, Daniel; Hasemann, Henning; Hauswirth, Manfred; Karnstedt, Marcel; Kleine, Oliver; Kröller, Alexander; Leggieri, Myriam; Mietz, Richard; Passant, Alexandre; Pfisterer, Dennis; et al. (Electronic Communications of the EASST, 2011)
The increasing convergence of the Internet as the global information backbone and embedded systems and sensors as key information providers on the state of the physical world to this backbone requires efficient design and imple- mentation methodologies which do not exist to date. Currently, the development of applications spanning both worlds is cumbersome and inefficient due to the lack of suitable frameworks and the limited understanding of the two development com- munities for the problems and underlying assumptions which need to be taken into account of “on the other side of the fence.” The goal of any methodology should be to provide the elegance and widespread adaption of Web-based standards in com- bination with the efficiency of the underlying embedded system and sensor layers, abstracting away “unnecessary” details while providing powerful paradigms which enable the necessary level of control in terms of APIs. This paper investigates uni- fied concepts, methods, and software infrastructures that support the efficient de- velopment of applications across the Internet and the embedded world, minimizing development efforts through flexible data and meta-data driven integration based on Semantic Web technologies.